What is the role of pulse oximetry screening in identifying neonatal morbidities other than critical heart diseases? - Şero, Leyla; Tunçel, Duygu; Akdeniz, Osman; Okur, Nilufer (Klinische Pädiatrie, 2025)
Pulse oximetry screening (POS) has been shown to be an effective, noninvasive screening method that can detect 50–70% of previously undiagnosed critical congenital heart diseases (CCHD). In this study, we sought to understand the role of POS in the detection of non-CCHD neonatal morbidities such as neonatal sepsis and polystemia. This cohort study was conducted in a central maternity hospital. Patients who failed POS were first evaluated by echocardiography, and then, other neonatal morbidities such as sepsis, polystemia and congenital pneumonia were evaluated. Overall, 29,840 infants had documented POS results in 34,806 live-born patients screened. A total of 301 (1%) infants had a positive test. A total of 23 (1.1%) patients had CCHD and significant congenital heart disease. Of those who failed pulse oximetry testing, noncardiac causes such as sepsis were observed in 101 (33.7%), congenital pneumonia in 16 (5.3%), polystemia in 32 (10.6%) and transient tachypnoea of the newborn in 52 (17.3%). POS can be a useful tool to aid clinical assessment in the diagnosis of significant non-cardiac morbidities such as sepsis, congenital pneumonia and polycythaemia in the newborn.
Keywords: congenital heart diseases; pulse oximetry screening; polystemia; sepsis; newborn